Brief behavioural intervention, delivered as standard care, to support physical activity engagement in men with prostate cancer: a pilot study protocol. Issue 1 (17th December 2018) - Fox, Louis; Wiseman, Theresa; Cahill, Declan; Fleure, Louisa; Kinsella, Janette; Van Hemelrijck, Mieke
Abstract : Introduction: Physical activity is beneficial to men with prostate cancer, but there remain barriers to fulfilling the potential of National Health Service trusts to support men with prostate cancer to be physically active. This article describes protocols for two pilot studies, each conducted in a different setting, designed to assess the potential of a behavioural intervention to affect patients' motivation to exercise. The intervention is theory based and inspired by recent empirical observations. Methods and analysis: The intervention consists of a 10 min talk, delivered to patients by a man with a history of prostate cancer treatment and a good experience of exercise, as part of their standard care. This talk either takes place in a preradical prostatectomy seminar (study one), or a post-treatment seminar designed to assist patients in adjusting to life after treatment (study two). Outcomes will be compared between patients attending the existing seminar format, and patients attending the novel seminar format. The two primary outcomes are: (1) differences in self-reported physical activity before and 90 days after the seminar and (2) the likelihood of the patient seeing an in-house exercise physiotherapist in those 90 days. Data on quality of life, fatigue and exercise behavioural regulations will also be captured at the same time points. Ethics and dissemination: These two projects have been approved by internal clinical audit committees due to their focus on service improvement. Findings from these pilot studies will be presented at oncology meetings and submitted for publication in academic journals.